2020
DOI: 10.1038/s41467-020-15632-y
|View full text |Cite|
|
Sign up to set email alerts
|

Sex-specific innate immune selection of HIV-1 in utero is associated with increased female susceptibility to infection

Abstract: Female children and adults typically generate more efficacious immune responses to vaccines and infections than age-matched males, but also suffer greater immunopathology and autoimmune disease. We here describe, in a cohort of > 170 in utero HIV-infected infants from KwaZulu-Natal, South Africa, fetal immune sex differences resulting in a 1.5-2-fold increased female susceptibility to intrauterine HIV infection. Viruses transmitted to females have lower replicative capacity (p = 0.0005) and are more type I int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The COVID-19 pandemic endangers global health. Studies have reported many differences between male and female COVID-19 patients in prevalence [ 11 ], disease severity, and mortality [ 12 , 13 ]; higher incidence, susceptibility, and mortality rates have been reported in men in several countries, and therefore the male sex is considered as a poor prognostic factor [ 11 , 29 ], as men are more susceptible [ 14 , 15 ] than women to viral infections, in particular to SARS-CoV-2, due to differences in innate immunity, steroid hormone levels, and factors related to sex chromosomes [ 16 , 30 , 31 ]. In the present study, a higher APACHE II score, which is a measure for acute physiology and chronic health [ 25 ], higher monocyte counts, and higher CRP and ALT levels were found in male COVID-19 patients than in their age- and severity-matched female counterparts, confirming the difference in disease severity and innate immune response between male and female COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic endangers global health. Studies have reported many differences between male and female COVID-19 patients in prevalence [ 11 ], disease severity, and mortality [ 12 , 13 ]; higher incidence, susceptibility, and mortality rates have been reported in men in several countries, and therefore the male sex is considered as a poor prognostic factor [ 11 , 29 ], as men are more susceptible [ 14 , 15 ] than women to viral infections, in particular to SARS-CoV-2, due to differences in innate immunity, steroid hormone levels, and factors related to sex chromosomes [ 16 , 30 , 31 ]. In the present study, a higher APACHE II score, which is a measure for acute physiology and chronic health [ 25 ], higher monocyte counts, and higher CRP and ALT levels were found in male COVID-19 patients than in their age- and severity-matched female counterparts, confirming the difference in disease severity and innate immune response between male and female COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response is a significant feature of sexual dimorphism, with women usually showing stronger immune responses. Sex differences in the immune response, especially the innate immune response, which have been implicated to influence infection outcomes in adults and children [ 16 ], are crucial in explaining the diversity of clinical features and for the efficient treatment of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, HIV develops strategies to evade IFN-I and to inhibit the functionality of the proteins regulated by IFN-I (Fenton-May et al, 2013), suggestive of a fundamental role of this pathway in viraemic control. Additionally, the presence of less fit, adapted viruses - well described for T cell immune escape(Roberts et al, 2015; Zimbwa et al, 2007) - could also contribute to the difference in IFN-I response observed in this study(Adland et al, 2020; Cohn et al, 2018; Iyer et al, 2017). By defining post-treatment control (‘PTC’) participants as those that rebounded more than 100 days after TI(Etemad et al, 2019), we identified an enrichment of platelet activation pathways as well as IFN-I.…”
Section: Discussionmentioning
confidence: 88%
“…Our previous work demonstrated that early treatment of HIV-infected adults, prior to peak viremia, prevents significant loss of circulating ILCs ( Kløverpris et al., 2016 ). To test this, we next examined the effect of early treatment initiation on circulating ILC subsets in a cohort of 27 in-utero -infected newborns (NBs), initiated on ART within minutes after birth ( Adland et al., 2020 ). ART was initially prophylactic (nevirapine and zidovudine) and then increased to triple therapy treatment from a median of 7 days post-partum (range 0–18 days), with all individuals remaining undetectable for plasma HIV RNA at 21 months of age ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral blood (PB) samples from children were obtained from the Ithemabalabantu pediatric cohort in Durban, KwaZulu-Natal (KZN), South Africa ( Muenchhoff et al., 2016 ) and from Stanger Hospital, Stanger, KwaZulu-Natal (KZN), South Africa ( Roider et al., 2019 ). PB samples from newborn/infants were obtained from the Ucwaningo Lwabantwana (meaning learning from children) infant cohort from Edendale, Mahatma Gandhi Memorial, Stanger and Queen Nandi Memorial Hospitals in KZN ( Adland et al., 2020 ). Tonsil tissue samples were obtained from pediatric patients undergoing routine tonsillectomy at Stanger Hospital, Stanger, KwaZulu-Natal (KZN), South Africa ( Roider et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%